Fun and fancy free [videorecording (DVD)] - Kinney, Jack; Lewis, Sinclair, 1885-1951; Shore, Dinah, 1917-1994; Bergen, Edgar, 1903-1978 (Walt Disney gold classic collection, 1999)
Jiminy Cricket introduces two stories: Bongo (based on a story by Sinclair Lewis) about a circus bear who wants to get back to the forest, and Mickey and the beanstalk, told by Edgar Bergen.